2010
DOI: 10.1186/1471-2105-11-s7-s4
|View full text |Cite
|
Sign up to set email alerts
|

T3SEdb: data warehousing of virulence effectors secreted by the bacterial Type III Secretion System

Abstract: BackgroundEffectors of Type III Secretion System (T3SS) play a pivotal role in establishing and maintaining pathogenicity in the host and therefore the identification of these effectors is important in understanding virulence. However, the effectors display high level of sequence diversity, therefore making the identification a difficult process. There is a need to collate and annotate existing effector sequences in public databases to enable systematic analyses of these sequences for development of models for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Type three secretion effector (TTSE) translocation signal peptide online program, such as ModLab (http://gecco.org.chemie.uni-frankfurt.de/T3SS_prediction/T3SS_prediction.html) (Lower & Schneider, 2009), T3SEdb (http://effectors.bic.nus.edu.sg/T3SEdb/predict.php) (Tay et al, 2010) and Effective T3 (http://www.effectors.org/index.jsp) (Amold et al, 2009) were used to predict the presence of TTSE for BipC. The domain family analysis was performed using Pfam protein families database (Finn et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Type three secretion effector (TTSE) translocation signal peptide online program, such as ModLab (http://gecco.org.chemie.uni-frankfurt.de/T3SS_prediction/T3SS_prediction.html) (Lower & Schneider, 2009), T3SEdb (http://effectors.bic.nus.edu.sg/T3SEdb/predict.php) (Tay et al, 2010) and Effective T3 (http://www.effectors.org/index.jsp) (Amold et al, 2009) were used to predict the presence of TTSE for BipC. The domain family analysis was performed using Pfam protein families database (Finn et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it was tenable to include proteins for Type III secretion system (T3SS) effectors and T3SS components. These were retrieved from PubMed as well as the T3SEdb database (Tay et al, 2010) . 2.1.1.7.…”
Section: Methodsmentioning
confidence: 99%
“…Through concerted actions, these effectors are known to modulate host cell functions, thereby contributing to the virulence of S. Typhimurium (82,83). Early in silico analyses of SrgE have provided conflicting predictions as to whether SrgE is a T3SS substrate (68)(69)(70)(71)(72). To test the hypothesis that SrgE is a T3SS, we used two different methods, a ␤-lactamase activity reporter assay and a split GFP system, to demonstrate that SrgE is indeed a T3SS effector delivered into host cells via T3SS2.…”
Section: Discussionmentioning
confidence: 99%
“…SrgE has a length of 488 amino acid residues, a molecular mass of 55 kDa, and a pI of 6.8. Two computer algorithms have suggested that SrgE possesses a type 3 secretion signal (68,69), while three other algorithms do not support this conclusion (70)(71)(72). SrgE also encodes a putative coiledcoil (CC) domain, located between residues 345 and 382.…”
mentioning
confidence: 99%